Rural tourism in the Tyumen region: potential of the Yarkovsky district - Poroshin, Oleg; Gaiduk, Maria; Sitnikova, Elena (project baikal, 2025)
The Tyumen region rivals historical regions of central Russia in its diversity of cultural heritage sites. Within Siberia, it can be considered one of the most interesting historical and cultural areas. In the Yarkovsky district of the Tyumen region, along with a wide variety of historical, cultural, and natural resources, there are unique sites associated with the lives of Saints Hermogenes, Bishop of Tobolsk and Siberia, Saint Andronicus, the New Martyr Father Feodor Raspopov, the family of the last Russian Emperor Nicholas Romanov, the birthplace of Grigory Rasputin, and others. These sites could serve as the basis for developing tourist routes on a variety of themes.
Keywords: Tyumen region; Yarkovsky district; cultural framework of the Tyumen region; historical and cultural heritage; rural tourism; wooden architecture